Young Consumers Behavior in Consuming Honey During the Covid-19 Pandemi: Case Study in Jakarta - S. Elsadibah; A. Apriantini; L. Cyrilla ENSD (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
Honey is a natural liquid produced by honey bees from plant flower essences or other parts of plants that contain various nutrients and bioactive compounds that can increase the body’s immunity during the COVID-19 pandemic. This research was conducted with the aim of analyzing the behavior of Jakarta young consumers in consuming honey during the COVID- 19 pandemic. The method used in this study was a survey using a questionnaire. About 204 young consumers between 20-30 years old in Jakarta who had consumed honey were interviewed and filled out a questionnaire. The selection of respondents was determined using a probability sample with a disproportionately stratified random sampling technique. Honey consumer respondents agreed to consume honey because honey can increase body immunity and increase stamina during the COVID-19 pandemic. The relationship between knowledge and situational factors with the decision to consume honey was tested using the Rank Spearman correlation test. Knowledge level and situational factors have a significant relationship with the decision to consume honey. This study showed that the higher the level of knowledge and situations that support consumers, such as the COVID-19 pandemic situation, the higher the level of honey consumption.